(untitled) (Swiss Medical Weekly, 2020)
AIMS OF THE STUDY Overweight and obesity in children and the harmful health consequences of these conditions throughout the course of their lives is a growing, worldwide public health problem. The purpose of this study is to evaluate the evolution of the prevalence of being overweight and obese among 5- to 6-year-old schoolchildren in Geneva from 2003 to 2018, and to compare it to other areas of Switzerland. METHODS A cross-sectional study at nine points in time, conducted in public schools from 2003–2004 to 2017–2018. During a systematic health check at school, data on the height and body weight of 5- to 6-year-old children attending public schools in the canton of Geneva were obtained. 12,918 girls and 13,395 boys were recruited for the study. Cole’s references were used to classify the body mass index. RESULTD In 2017–18 the combined prevalence of overweight and obesity was 14.6%, of which 10.3% were overweight (14.5% for girls and 5.9% for boys) and 4.3% were obese (4.5% for girls and 4.2% for boys). For girls, we observed a non-significant increase in the prevalence of overweight of 2.5 points (p = 0.14) between 2003–04 and 2017–18, as opposed to boys, where we observed a non-significant downward trend (−2.7 points, p = 0.06) over the same period. A relatively marked and statistically significant increase in the prevalence of obesity (1.9 points, p = 0.0130) since 2010 was observed for both sexes in this age group. CONCLUSION From 2003 to 2018 we observed a stabilisation in the prevalence of overweight and obesity in childhood, which is consistent with results from other Swiss cities, as well as in some other countries worldwide. The significant increase in obesity observed since 2010 will have to be monitored and justifies pursuing public health policies and potentially some more aggressive approaches.